Can the coronavirus infection penetrates the brain resulting in sudden anosmia followed by severe neurological disorders? (2020)
Serious of unpredictable drawbacks of Coronavirus 2019 (COVID-19) infectious disease caused by SARS-COV-2 on the nervous system, have been widely noticed among the huge number of infected people. It was found that this type of newly revolving pandemic infection mainly infects the human respiratory tract causing mild to moderate symptoms, however, the hidden door side of COVID-19 is via penetrating the brain, revealing a huge threat especially to elderly people who are more susceptible to its severe side effects and even death to more extent. Almost 80% of COVID-19 patients suffer from severe neurological manifestations including dizziness, headache, unconscious, irritability, dysfunction in smell, and taste accompanied by muscle fatigue. Herein, we are trying to address the direct neuroinvasive pathway of COVID-19 into human brain cells which is mainly through the olfactory route leading to longterm neurological complications. In addition to highlighting the ability of COVID- 19 infection to intensify a pre-existing AD to a more prominent severe stage. The other thing to emphasize is whether AD patients with a highly prominent activation of local immune responses are more or less exposed to getting infected with COVID-19. Along with underlying the hypothesis that the susceptibility to COVID-19 infection may lead to a future risk for neurodegenerative diseases including Alzheimer’s disease (AD).